Religious non-profit organisations’ (RNPOs) financial management in Malaysia: key drivers and insights from the literature - Rozaidy Mahadi; Noor Kaziemah Sariman; Ag Kaifah Riyard Kiflee (AMH International, 2024)
This study examines the financial management practices of Religious Non-Profit Organisations (RNPOs) in Malaysia, addressing a critical need for improved governance and transparency across religiousbased non-profit organizations. Despite the vital role of RNPOs in supporting socio-economic development, existing research primarily focuses on donor intentions rather than the organizational perspective, leaving a significant gap in understanding financial practices. Employing a thematic analysis of key studies, this research explores drivers of financial sustainability, including standardized reporting, accountability measures, and donor engagement strategies. The findings reveal notable disparities in financial disclosures, particularly between Islamic and non-Islamic RNPOs, and highlight the importance of financial integrity in building donor trust. This study proposes a comprehensive approach to enhance financial practices, advocating for the development of standardized reporting frameworks and improved governance mechanisms tailored to the unique needs of multi-faith RNPOs. The insights strengthen the financial credibility and operational effectiveness of RNPOs, providing a foundation for future research and policy development to sustain this essential community organization.